OBE Curriculum-Based E-RPS Application Development: An Innovative Approach to Improve Planning Quality - Siti Qomariah; Jumiyati Jumiyati; Muhammad Irfan Anwari (Unversitas Muhammadiyah Mataram, 2025)
This study aims to develop an Electronic Semester Learning Plan (E-RPS) application based on the Outcome-Based Education (OBE) curriculum to address challenges in curriculum management, such as unstructured data, non-uniform standards, and inefficiencies in manual preparation. The study employed the Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data collection included interviews, questionnaires, and documentation, with respondents selected using a snowball sampling technique. Application performance was tested using black-box and beta testing methods, with Likert-scale-based questionnaires for user feedback. Data analysis focused on usability, functionality, and efficiency. The E-RPS application integrates curriculum elements (CPL, CPMK, and Sub-CPMK) and standardizes the RPS preparation process. It automates workflows, enhances data accessibility, and provides collaborative features for lecturers and administrators. Testing results showed an average user satisfaction rate of 87%, validating the application's effectiveness in improving the quality and accuracy of RPS preparation, aligning with OBE principles. This research provides a practical solution to streamline RPS preparation, enhance transparency in curriculum management, and support international accreditation efforts. The findings contribute to the theoretical understanding of integrating technology with OBE frameworks and offer a replicable model for higher education institutions aiming to improve curriculum quality and compliance